Analisis Usahatani Nilam (Pogestemon cablin Benth) di UPT Pohorua Kecamatan Maligano Kabupaten Muna - Wartini, Ni Komang; Geo, Laode; Rosmawaty, Rosmawaty (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2018)
The purpose of this research was it know the input of patchouli farming (land, labor, and production means such as seeds, medicines, and fertilizers), to know the income of patchouli farmers in UPT Pohorua Maligano Subdistrict Muna Regency and to know the feasibility of patchouli farming at UPT Pohorua financially District Maligano Muna Regency. Conducted in March to May 2017. The sampling was done by census method which was 27 peanut farmers. Pursuant to result of research indicate that Input of patchouli farm (land, labor and production facilities such as seeds, medicines, and fertilizers) available in research area. Even the revenues obtained by patchouli farmers in UPT Pohorua Maligano sub-district of Muna Regency that is Rp 224,952,174 and the total cost obtained by patchouli farming for Rp.38,037,826. Based on financial analysis, the R / C Ratio is 2.95. Any patchouli investment expenditures of 1 unit or 1 rupiah will result in a financial gain of 1.95. In this case the meaning that the investment expense of patchouli farm will result in investment of 2.95. While the result of capital productivity (Î¼ / C) Ratio generated equal to 4,57% where the value of patchouli seed production productivity greater than prevailing bank interest is 4.50%.